Adoption of POS Technology in MSMEs: A Case Study of Ecoprint Forum, Purbalingga - Prasetyo, Novian Adi; Bahtiar, Arief Rais; Febriani, Atik; Saputra, Wahyu Andi (LPPM Universitas Jambi, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are businesses operated by individuals, households, or small organizations, commonly characterized by limited annual turnover, assets, and number of employees. A significant issue among MSMEs is the lack of separation between business and personal finances, leading to ineffective financial management and the absence of professional systems. This challenge often results in difficulties in tracking inventory and transaction data accurately. In response to this issue, this community engagement project aims to implement a Point of Sale (POS) application as a practical solution for improving financial and operational efficiency within MSMEs. The initial implementation was conducted with a partner MSMEs in Purbalingga, Alima Makmur, which operates in retail paint. To further evaluate the benefits and adaptability of the POS system, the implementation was extended to members of the Ecoprint MSMEs Forum in Purbalingga. The results show that 4 out of 5 MSMEs successfully adopted and independently operated the POS application. This study contributes to the growing body of knowledge on digital adoption in micro-enterprises and provides practical implications for enhancing business sustainability through simple technological interventions.